Multi-drug resistant (MDR) and extensively drug-resistant (XDR) bacteraemia rates among cancer patients in an oncology hospital in eastern India: an 11-year retrospective observational study - Satyam Mukherjee; Maitrayee Sarkar De; Gaurav Goel; Arpita Bhattacharyya; Indranil Mallick; Deepak Dabkara; Jaydip Bhaumik; Manas Kumar Roy; Piyali Bose Majumdar; Soumyadip Chatterji; Sudipta Mukherjee; Sanjay Bhattacharya; et al. (Elsevier, 2023)
Summary: Background: Trend analysis of bacteraemias caused by multi-drug resistant (MDR) and extensively drug resistant (XDR) bacteria helps to assess efficacy of infection prevention and control (IPC) practices. Data on the trends of MDR and XDR bacteraemias are lacking from cancer patients in India. Aims: To report antibiotic resistance rates over time in bacteraemias and to assess the effect of IPC practices where patient isolation facilities were limited on the rates and trends of MDR and XDR bacteraemias from a cancer centre in eastern India. Methods: A retrospective observational study was conducted in a specialist cancer hospital in India from 2011 to 2021. The study included both patients with haematological and solid organ malignancy. Data on blood cultures and surveillance culture samples were analysed. Blood cultures were processed using BACT/ALERT® (bioMérieux, Marcy-l'Étoile, France) and the identification and antibiotic susceptibilities of bacteria were performed using VITEK® 2 (bioMérieux, Marcy-l'Étoile, France). Surveillance cultures for MDR/XDR bacteria were performed on a subset of patients and processed based on a modified method described previously. Findings: 3rd-generation cephalosporin-resistant Gram negative bacilli were the commonest cause of MDR bacteraemia (57.6%) followed by carbapenem resistant organisms (CRO) (35.7%). Bacteraemias caused by vancomycin-resistant enterococci (VRE), meticillin-resistant Staphylococcus aureus (MRSA) and colistin-resistant Gram negative bacilli were responsible for 1.3%, 2.3% and 3.0% of laboratory confirmed bloodstream infections (BSI) respectively. The ranges of the rates of MDR/XDR BSI per 1000 in-patients during the study period were: MRSA (1-1.18), VRE (0-0.88), 3rd generation cephalosporin-resistant Gram negative bacilli (10.10-20.32), CRO (5.05-13.07) and colistin-resistant Gram negative bacilli (E. coli, Klebsiella, Pseudomonas aeruginosa, Acinetobacter spp (0-1.3). Surveillance cultures collected from a subset of patients showed ranges of MRSA detection in 0-2.11%, VRE in 1.67%-7.49%, 3rd generation cephalosporin-resistant Gram negative bacilli in 55%-89.91% and carbapenem resistant Gram negative bacilli in 18.33%-31.11% of patients. Conclusion: This is one of few studies providing trend data for MDR/XDR bacteraemia rates among cancer patients in India over a decade. In a high prevalence setting it was possible to keep the rates of MDR/XDR bacteraemia controlled with IPC strategies and without adequate isolation facilities. The results are of potential interest to policy makers, IPC specialists and clinicians.